2002
DOI: 10.1136/heart.87.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Value of plasma B type natriuretic peptide measurement for heart disease screening in a Japanese population

Abstract: Background: Conflict exists regarding the usefulness of measuring plasma B type natriuretic peptide (BNP) concentrations for identifying impaired left ventricular (LV) systolic function during mass screening. Various cardiac abnormalities, regardless of degree of LV dysfunction, are prone to carry a high risk of cardiovascular events. Objective: To examine the validity of plasma BNP measurement for detection of various cardiac abnormalities in a population with a low prevalence of coronary heart disease and LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 33 publications
3
92
0
1
Order By: Relevance
“…19,23) Therefore, plasma BNP levels may be a potential screening marker for identifying individuals with asymptomatic mild heart failure as well as those at high risk for moderateto-severe heart failure because of various forms of structural heart disease. 24) The relationship between angiogenesis biomarkers and BNP levels has not been prospectively evaluated. In our study, 2.5 ± 3.3 1.6 ± 1.…”
Section: Discussionmentioning
confidence: 99%
“…19,23) Therefore, plasma BNP levels may be a potential screening marker for identifying individuals with asymptomatic mild heart failure as well as those at high risk for moderateto-severe heart failure because of various forms of structural heart disease. 24) The relationship between angiogenesis biomarkers and BNP levels has not been prospectively evaluated. In our study, 2.5 ± 3.3 1.6 ± 1.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that plasma BNP can be elevated in subjects with subclinical structural heart disease. 35 We therefore speculate that the elevated levels of plasma BNP in the patients with worse outcomes denote mild structural heart disease such as subclinical cardiac dysfunction, including mildly elevated intracardiac pressure and volume and, possibly, myocardial ischemia. These individuals might be prone to be at risk for HF and coronary heart disease.…”
Section: Tion Of Long-term Anticoagulation Therapy (Re-ly) and The Apmentioning
confidence: 92%
“…However, this value is comparable to that in our previous report conducted in a Japanese population participating in a multiphasic health examination programme. 13) As the predominant etiology in this instance was coronary heart disease, the low prevalence of left ventricular systolic dysfunction in this population may have been due to the low prevalence of coronary heart disease. Clinical Implications: The most prevalent precursors of CHF in the general population are hypertensive cardiac hypertrophy, coronary heart disease, and a combination of the two.…”
Section: Discussionmentioning
confidence: 99%
“…This was done because a previous study of ours using identical assay methodology showed that this was the most useful cutoff point for the detection of several types of structural cardiac disorder. 13) Another limitation of the present study was the possibility of bias in the selection of the subject population. However, the trends in the prevalence of hypertension, history of stroke, serum total cholesterol levels, and body mass index in the present cohort were similar to those reported in a randomly selected Japanese adult population.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation